PENGARUH PENGGUNAAN MEDIA PUZZLE TERHADAP PENINGKATAN KEMAMPUAN KOGNITIF ANAK USIA 4–5 TAHUN DI KOBER AL IKHLAS - Enung Nuraeni; Yusuf Hidayat; Rifa Fauziyatul Azizah (Jurnal Intisabi, 2026)
This study was motivated by the low cognitive ability of early childhood aged 4–5 years at Kober Al Ikhlas, particularly in logical thinking, simple problem-solving, and symbol recognition. The study aimed to determine the effect of puzzle media on improving the cognitive ability of early childhood aged 4–5 years at Kober Al Ikhlas, Lumbung District, Ciamis Regency. This study employed a quantitative approach using a pre-experiment through One Group Pretest-Posttest Design. The participants consisted of 15 early childhood who were taken with saturated sampling technique from group A aged 4–5 years. In addition, the data were gethered through observation and documentation. Data analysis was conducted using descriptive statistics, N-Gain analysis, and the Wilcoxon Signed Rank Test. The results revealed that the average cognitive ability score increased from 15.7 in the pretest to 25.5 in the posttest. The N-Gain result was 0.35 or 35%, which was categorized as moderate improvement. Furthermore, the Wilcoxon Signed Rank Test showed a significance value of 0.001 < 0.05, indicating a significant effect of puzzle media on improving early childhood's cognitive ability. Therefore, puzzle media can be used as an alternative learning media to improve early childhood’s cognitive development.